2014
DOI: 10.1155/2014/747293
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Identification and Treatment of Depression in Heart Transplant Patients

Abstract: Background. The effects of clinical depression after orthotopic heart transplantation (OHT) are relatively unknown. The purpose of this study was to evaluate the impact of depression on outcomes after OHT. Methods. We performed a single center retrospective review of 102 consecutive patients who underwent OHT at Northwestern Memorial Hospital from June 2005 to October 2009. The diagnosis of depression was obtained from attending physician documentation. The primary endpoints were all-cause mortality (ACM), hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 50 publications
1
14
0
1
Order By: Relevance
“…The PHQ‐9 is a brief measure of depressive symptoms that has been validated for the assessment of clinical depression and as a screening measure for elevated depression. The PHQ‐9 has been used extensively among medical populations, including transplant patients Centers for Epidemiologic Study of Depression (CESD) .…”
Section: Methodsmentioning
confidence: 99%
“…The PHQ‐9 is a brief measure of depressive symptoms that has been validated for the assessment of clinical depression and as a screening measure for elevated depression. The PHQ‐9 has been used extensively among medical populations, including transplant patients Centers for Epidemiologic Study of Depression (CESD) .…”
Section: Methodsmentioning
confidence: 99%
“…Several studies reported no association between psychosocial factors and mortality [912], while others have found that several psychiatric risk factors and social/demographic characteristics correlated with post-transplant morbidity [8]. As a result, the role of psychosocial factors on heart transplant outcomes requires further evaluation [13].…”
Section: Introductionmentioning
confidence: 99%
“…La mayoría de estudios realizados hasta la fecha, refieren una morbilidad psiquiátrica elevada durante todo el proceso de TC, principalmente a expensas de trastornos depresivos y de ansiedad. Sin embargo, la influencia de las variables psiquiátricas en los resultados del TC no está claro y sólo un número limitado de estudios han examinado el papel pronóstico que ejercen, obteniendo resultados dispares (Zipfel et al, 2002;Owen et al, 2006;Havik et al, 2007;Okwuosa et al, 2014).…”
Section: Psicopatología Y Morbilidad Psiquiátricaunclassified